Competitive intelligence: meanings, concepts and applications / Adnan Jamaludin - Jamaludin, Adnan (Faculty of Information Management, Universiti Teknologi MARA, 2014)
Competitive intelligence or in short known as Cl is a tool for strategic management that organizations could benefit from. Cl provides clear guidance to business companies about what to expect based on the intelligence gathered through the Cl process. Although Cl has been playing its important role in business companies, there are still many who fail to capitalize and reap its potentials and benefits. This is because the precursor to Cl establishment in any business companies is to understand the Cl concepts before it can be put into practice. This paper attempts to highlight some of the many concepts that are deemed important in carrying out the Cl work. The concepts could also be used as a framework for future research in Cl.